Complexity of scar and ventricular arrhythmias in dilated cardiomyopathy of any etiology: Long‐term data from the SCARFEAR (Cardiovascular Magnetic Resonance Predictors of Appropriate Implantable Cardioverter‐Defibrillator Therapy Delivery) Registry. Issue 4 (17th April 2018) - Pedretti, Stefano; Vargiu, Sara; Baroni, Matteo; Dellegrottaglie, Santo; Lanzarin, Barbara; Roghi, Alberto; Milazzo, Angela; Quattrocchi, Giuseppina; Lunati, Maurizio; Pedrotti, Patrizia
Abstract : Background: Late gadolinium enhancement (LGE) assessed with cardiovascular magnetic resonance (CMR) correlates with ventricular arrhythmias and survival in patients with structural heart disease. Whether some LGE characteristics may specifically improve prediction of arrhythmic outcomes is unknown. Hypothesis: We sought to evaluate scar characteristics assessed with CMR to predict implantable cardioverter‐defibrillator (ICD) interventions in dilated cardiomyopathy of different etiology. Methods: 96 consecutive patients evaluated with CMR received an ICD. Biventricular volumes, ejection fraction, and myocardial LGE were evaluated. LGE was defined as "complex" (Cx‐LGE) in presence of ≥1 of the following: ischemic pattern, involving ≥2 different coronary territories; epicardial pattern; global endocardial pattern; and presence of ≥2 different patterns. The primary endpoint was occurrence of any appropriate ICD intervention. A composite secondary endpoint of cardiovascular death, cardiac transplantation, or ventricular assist device implantation was also considered. Results: During a median follow‐up of 75 months, 30 and 25 patients reached the primary and secondary endpoints, respectively. Cx‐LGE was correlated with a worse primary endpoint survival (log‐rank P < 0.001). Cx‐LGE and right ventricular end‐diastolic volume were independently associated with the primary endpoint (HR: 3.22, 95% CI: 1.56–6.65, P = 0.002; and HR: 1.06, 95% CI: 1.00–1.12, P = 0.045, respectively), but not with the secondary endpoint. Conclusions: Cx‐LGE identified at CMR imaging seems promising as an independent and specific prognostic factor of ventricular arrhythmias requiring ICD therapy in dilated cardiomyopathy of different etiologies.